The integrated microfluidic photocatalytic planar reactor under continuous operation - Ge, Xue-hui; Wei, Nanjie; Hu, Xinyue; Xie, Qinyin; Wang, Xiaoda; Li, Ling; Qiu, Ting (Frontiers in Chemical Engineering, 2024)
An integrated microfluidic planar reactor is essential in efficient enhanced photocatalytic water treatment. Optimization of catalysts is currently under intense study due to the need to enhance microreactors' performance. This paper presents a high-efficiency photocatalytic microreactor by combining a planar microreactor and a high-efficiency photocatalyst. TiO2 nanoparticles doped with Y and Yb were prepared to improve the photocatalytic reaction efficiency. The planar microreactor provides a convenient platform for studying photodegradation under various conditions such as different temperatures, flow rates, light irradiation(UV and Vis), and reaction modes (continuous and intermittent). First, better performance is achieved in the Y, Yb/ TiO2, and TiO2 microreactors compared to conventional bulk reactors because of good photodegradation and high reaction rate. Then, The Y, Yb/ TiO2 film microreactor exhibits not only an efficient catalytic activity with UV light but also a higher photocatalytic activity under visible light irradiation than that achieved by a TiO2 film microreactor. The reaction rate constant of the Y, Yb/ TiO2 film microreactor is about 0.530s-1, which is twice that of the TiO2 film microreactor. Moreover, the performances under continuous and intermittent reactions are compared to evaluate the stability of the microreactor, building the foundation of the practical application of continuous water treatment in the microreactors.